PENGARUH STRUKTUR KEPEMILIKAN, KINERJA KEUANGAN DAN CORPORATE SOCIAL RESPONSIBILITY TERHADAP NILAI PERUSAHAN - Fahri Hapsanto, - (2019)
The purpose of this study is to tested the influence of Ownership Structure, Financial Performance, and Corporate Social Responsibility on Company Value. This study used manufacturing goods and consumption sector there are 28 companies listed on Indonesian Stock Exchange (BEI) as the sample in 2014 until 2017. The sampling technique used in this research was purposive sampling method. The data used in this research was secondary data. The secondary data used in this research were from the annual report which was published in the official website of Indonesian Stock Exchange (BEI) www.idx.co.id. Hypothesis examination in this research used Multiple Linear Regression Analysis with SPSS 23 Programme and 5% of significant level. The result of this research shows that (1) Ownership Structure has no significant influence on Company Value, (2) Financial Performance has significant influence on Company Value, (3) Corporate Social Responsibility has no significant influence on Company Value.